Access to Affordable Health: A Care Delivery Model of GNRC Hospitals in North-Eastern India - Nomal Chandra Borah; Priyanka Borah; Satabdee Borah; Madhurjya Borah; Purabi Sarkar (Int. J. Integr. Care, 2024)
Introduction: The healthcare delivery system of Assam faces several challenges to provide affordable, accessible and quality care services. GNRC (Guwahati Neurological Research Center) is the first super-speciality hospital to address many of these gaps by delivering integrated affordable healthcare services to the populations of Assam and other parts of North-eastern India. Description & Discussion: This paper describes the implementation of a care delivery model which provides integrated care delivery services through linking hospitals to primary healthcare services, including preventive, promotive, and curative care, along with delivering easily accessible and affordable care to the people of Assam and other parts of North-eastern India. Conclusion: The proposed model is the first innovative approach from Northeastern India, Assam, to deliver affordable, accessible and patient-centric hospital led community-based preventive, promotive, and primary, secondary, and tertiary hospital-based care. It is anticipated that GNRC's Affordable Health Mission will help redesign and integrate the way primary, secondary and tertiary healthcare is delivered to the population of Assam in helping patients manage their own health and reduce the numbers that needs to be admitted to secondary care and tertiary care by improving patients' independence and well-being as well as dramatically reducing the cost to the overall health system.
Keywords: Accountability; Community-based accountability; National Rural Health Mission; Belief structures; Problematisation; Policy implementation